‘On the mountain, the world is still all right’: nature connections in context and the Covid journey of young adults in Austria - Bork-Hüffer, Tabea; Wächter, Leonie; Hitchings, Russell (People and nature, 2024)
Research and policy during the Covid-19 pandemic often dovetailed with an established interest in how nearby urban nature spaces can encourage human well-being. Yet, to define the focus upfront in this way is to overlook the many ways in which different groups may draw on experiences in diverse natural environments to get through challenging times. This paper draws on a qualitative study with 98 university students in Innsbruck, Austria. As part of a co-production approach, and using a range of exploratory and inductive methods, we examined how they coped with lockdown restrictions and other challenges to everyday life during the pandemic between March and November 2020. The study's longitudinal design reveals how their nature relations evolved over the lifetime of the pandemic. Participants showed a strong identification with the Alpine nature surrounding Innsbruck and deeply mourned opportunities to go there during quarantine at the start. With the relaxation of restrictions, they briefly celebrated the return of access to these spaces before nature experiences were soon blended back into their everyday lives as before. The findings present an account of nature spaces being valued during the pandemic precisely because they were away from urban spaces nearby that had come to feel strange as a result of the lockdown restrictions. This leads us to reflect on the importance of how exactly people engage with local nature and how nature connections change in response to the evolving pressures and preoccupations that shape everyday life, both for young people and others. We emphasise the value of contextual sensitivity in future research and policy hoping to foster nature benefits, both during crisis situations such as these and more generally. Read the free Plain Language Summary for this article on the Journal blog.
Gesehen am 09.04.2025